Unlocking potential: the impact of emotional intelligence on quality of life and academic success of students with disabilities - Elshaer, Ibrahim A.; Sobaih, Abu Elnasr E.; Alyahya, Mansour; Azazz, Alaa M. S.; Khan, Mahmood A. (Frontiers in Psychology, 2025)
BackgroundDespite the importance of emotional intelligence (EI) for academic performance of university students with disabilities, limited research was undertaken to address this issue.ObjectivesThis research investigates the impact of EI on quality of life (QoL) and academic performance among university students with disabilities. Drawn on Salovey and Mayer’s EI framework, this research examines the impact of four main EI dimensions: self-emotion appraisal, others’ emotion appraisal, use of emotion, and regulation of emotion, on academic success through the lens of QoL.MethodsA quantitative, cross-sectional research design was employed, including a sample of 328 university students with several types of disabilities. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze the obtained data and test the justified hypothesized relationships.ResultsThe results demonstrate that the higher levels of EI are significantly related to improved QoL, which consequently has a positive impact on students’ academic performance. The results confirmed that QoL demonstrated partial mediating effects in the relationship between EI and academic achievements, signaling that EI can contribute to academic success both directly and indirectly by fostering students’ overall QoL.ImplicationsThe study contributed to the current literature by emphasizing the interconnections of emotional competences, quality of life, and academic performance, and provided practical implications for interventions aimed at supporting this vulnerable population.